Physicality in Postcolonialism: Tensions at the Asian Rural Institute - Senda-Cook, Samantha (Frontiers in Communication, 2021)
The Asian Rural Institute (ARI) is a transnational NGO that has a unique model of education and was founded in response to Japan’s role as a colonizer. It invites participants from around the world to learn sustainable agriculture, servant leadership, and community advocacy at their campus in Tochigi, Japan. Postcolonial studies has a strong foundation of analyzing physical elements such as bodies and space and their role in both controlling colonized people and resisting colonizers. I argue that the complications of postcolonial and racial relationships manifest physically through movement and shared space at ARI, both of which operate as tensions that support (and sometimes undermine) self-determination and survivance, key characteristics of decolonization. This analysis contributes to postcolonial scholarship by providing another means of conceptualizing movement and linking space to consubstantiation.